A New Developed Photoelectrochemical Cell for Hydrogen Generation - M. Shoikhedbrod (International Journal of Photochemistry and Photochemical Research, 2024)
There are many methods for the industrial production of hydrogen, including: steam reforming of methane and natural gas; coal gasification; biotechnology; electrolysis of water, etc. The most effective method of obtaining of pure hydrogen is the use of photoelectrochemical cell. Photoelectrochemical cells produces hydrogen directly from solar energy. In a photoelectrochemical cell, a silicon semiconductor with an anode attached to it, immersed in an aqueous electrolyte solution and excited by two photons of light, forms two hydrogen cations and half an oxygen molecule, which floats from the anode to the free surface of water in the form of a gas bubble. The resulting two hydrogen cations, reaching of the cathode, form a gaseous hydrogen molecule, which in an aqueous electrolyte solution takes the form of an electrolytic bubble of gaseous hydrogen that floats from the cathode to the free surface of the aqueous electrolyte solution. However, the existing photoelectrochemical cells, used today are expensive, have limitations in materials, which significantly hinders their effectiveness. The article presents a developed hydrogen generator that produces pure hydrogen at a below market price using a photo-electrochemical cell, having a specially designed electrolysis base, including a fire hose material membrane, located between a silicon semiconductor with attached mesh anode; a made from burnt graphite cathode and mechanism for adjusting the gap between electrodes at the bottom of the photoelectrochemical cell. The design of a large reactor with built-in photoelectrochemical cells will be considered.
Keywords: Electrolysis base; Hydrogen and oxygen generator; Membrane from a fire hose; Photoelectrochemical cells; Solar Energy; Water electrolysis